Penerapan Terapi Senam Yoga terhadap Penurunan Tekanan Darah Pada Pree Lansia Yang Mengalami Hipertensi - Umi Hanik; Ambarwati Ambarwati (Jurnal Sains dan Kesehatan, 2022)
Yoga can also stimulate the release of endorphin hormones, this hormone is produced by the body when relaxed/calm which functions as a natural sedative produced by the brain so that it can create a sense of comfort and increase endorphin levels in the body to reduce high blood pressure. Yoga is included in alternative forms of physical activity such as yoga exercise which can help achieve physical exercise levels so that the body becomes relaxed, this physical exercise is recommended for individuals, everyone including the elderly, teenagers and pregnant women can do yoga.